Trace element and sulphur isotope variations of sulphides in the Koperberg Suite, O'okiep Copper District, Namaqualand, South Africa: implications for formation of sulphides and the role of crustal sulphur assimilation - Marima, Edmore (Rhodes University, Faculty of Science, Department of Geology)
The major economic copper sulphide deposits hosted in the late Mesoproterozoic intrusions of the Koperberg Suite in the O'okiep Copper District immediately overlie sulphur-bearing paragneisses of the Khurisberg Subgroup in an otherwise low-sulphur granitic basement. The dominant sulphide assemblage (chalcopyrite and bornite) hosted in the Koperberg Suite is also atypical of the intermediate solid solution (iss) assemblage (chalcopyrite and pyrrhotite) observed in most Cu-Ni magmatic sulphide deposits. This study presents sulphur isotope and in-situ trace element analysis of sulphides from the Koperberg Suite and the Khurisberg Subgroup with the view of placing constraints on the role of sulphide-bearing supracrustal metasedimentary of the Khurisberg Subgroup as a source of additional sulphur in the genesis of these deposits, and ore-forming (sulphide formation) processes which result in trace element variations registered by sulphides hosted in the Koperberg Suite. The high concentrations (up to 2100 ppm) of monosulphide solid solution (mss)-incompatible trace elements (e.g., Te, Se, Bi, Ag, Pb), and the depletion in Ni and Co (<40 ppm) of sulphides hosted in the Koperberg Suite are instead consistent with the derivation of such sulphides from a Cu-rich sulphide melt which segregated from a Ni-rich sulphide melt prior to magma emplacement in the middle crust, in agreement with one of the petrogenetic models for the Koperberg Suite proposed in the existing literature. The low S/Se ratios ( Ì´650-10300) of sulphides hosted in the Koperberg Suite and the high S/Se ratios ( Ì´18800-56000) registered by the main sulphide phase (pyrite) in the Khurisberg Subgroup argues against crustal contamination of the Koperberg Suite magmas by the Khurisberg Subgroup. The S/Se and Cu/S ratios of coexisting bornite and chalcopyrite hosted in the Koperberg Suite are positively correlated with the bornite modal abundance in the Koperberg Suite. Such trends are interpreted to be consistent with progressive oxidation of sulphide melt, a process which results in the crystallisation of iss-bornite assemblage and/or replacement of iss with bornite due to the enrichment of Cu and depletion in S of the sulphide melt. The oxidation of sulphide melt is likely to have been effectuated by the fractional crystallisation of mss in a prior sulphide melt segregation event and/or the fractional crystallisation of Fe2+-dominated silicate phases. Fractionation of the Cu-rich melt sulphide melt (segregated from mss) also tends to enrich the residual sulphide melts in Se. Thus, the chalcopyrite-dominated assemblage with S/Se ratios of Ì´1300-10200 observed in the less basic rocks in the Koperberg Suite (leucodiorites and leuconorites) is interpreted to have formed from the least evolved sulphide melt, whereas the bornite-dominated assemblage with S/Se ratios of Ì´650-5500 observed in the more mafic members of the Koperberg Suite (orthopyroxenites and norites) is interpreted to have formed from the most evolved sulphide melt. The áºŸ34S isotopic signatures in sulphides of the Koperberg Suite (-1.4 to +1.91"°) and the proposed contaminant, the Khurisberg Subgroup (-1.2 to +3.5"°), overlap with the those of the Koperberg Suite below the Khurisberg Subgroup (+0.74"°) and typical mantle-derived magmatic rocks (0 Â± iv 2"°). Hence, the sulphur isotope variations are inconclusive as an indicator of possible crustal sulphur assimilation into the intruding mantle magma. However, considering the trace element systematics and the sulphur isotope data, the Koperberg magmas likely attained sulphur saturation at deeper crustal levels.
Keywords: Sulfur Isotopes; Magmatism -- South Africa -- Namaqualand; Sulfides; Koperberg Suite (South Africa); Copper sulfide; Sulfur -- Absorption and adsorption